2012
DOI: 10.1039/c2cs35076a
|View full text |Cite
|
Sign up to set email alerts
|

Particles, air quality, policy and health

Abstract: 21 22The complexity of ambient particle composition considerably complicates pinpointing specific 23 causal associations between exposure to particles and adverse human health effects, the 24 contribution of different sources to ambient particles at different locations, and the consequent 25 formulation of policy action to most cost-effectively reduce harm caused by airborne particles. 26Nevertheless, the coupling of increasingly sophisticated measurements and models of particle 27 composition and epidemiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
341
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 592 publications
(357 citation statements)
references
References 295 publications
(366 reference statements)
3
341
0
Order By: Relevance
“…[3][4][5][6] Up to half of global CCN is estimated to originate from NPF. 5,6 In addition, particles have well-known deleterious impacts on human health 7,8 and visibility. [9][10][11] Despite these impacts, the underlying mechanisms and the potential species driving NPF are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Up to half of global CCN is estimated to originate from NPF. 5,6 In addition, particles have well-known deleterious impacts on human health 7,8 and visibility. [9][10][11] Despite these impacts, the underlying mechanisms and the potential species driving NPF are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 2c-d show the PND spectrums obtained during the drilling and cutting of samples of hardened concrete. The peak PND values obtained were 37.10×10 4 and 118.80×10 4 cm -3 , respectively, being ~3.5 and 8-times higher than the background peak PNDs. A significant increase in nucleation mode particles was observed with cutting producing a greater release of new particles (over background) than drilling, reflecting the larger surface area of concrete subject to abrasion.…”
Section: Particle Size Distributionsmentioning
confidence: 68%
“…It was shown that the EF not only depends on PNCs and PMC but also depends on volume of the drilled or cut area and on the size and sharpness of the cutting tool. The EFs during the mixing with GGBS, PFA, drilling and cutting activities were 8.25±4.09 ×10 4 , 14.95±7.83 ×10 4 , 18890.12±4944.36 ×10 4 and 80905.12±56954.83 ×10 4 s -1 kg -1 , respectively. Relatively higher EF during mixing with PFA compared with GGBS could possibly be due to the differences in hydration and reaction rates of GGBS and PFA with the Portland cement [47].…”
Section: Emission Factorsmentioning
confidence: 97%
See 2 more Smart Citations